Interpreting silent artefacts : petrographic approaches to archaeological ceramics - Quinn, Patrick S. (Archaeopress Publishing Ltd, 2010)
This volume presents a range of petrographic case studies as applied to archaeological problems, primarily in the field of pottery analysis, i.e. ceramic petrography. Petrographic analysis involves using polarising optical microscopy to examine microstructures and the compositions of rock and mineral inclusions in thin section, and has become a widely used technique within archaeological science. The results of these analyses are commonly embedded in regionally specific reports and research papers. In this volume, however, the analytical method takes centre stage and the common theme is its application in different archaeological contexts.